New Insights Into the Biosynthesis of Typical Bioactive Components in the Traditional Chinese Medicinal Fungus Cordyceps militaris - Wu, Xiuyun; Wu, Tao; Huang, Ailin; Shen, Yuanyuan; Zhang, Xuanyu; Song, Wenjun; Wang, Suying; Ruan, Haihua (Frontiers in Bioengineering and Biotechnology, 2021)
Cordyceps militaris, a traditional medicinal ingredient with a long history of application in China, is regarded as a high-value fungus due to its production of various bioactive ingredients with a wide range of pharmacological effects in clinical treatment. Several typical bioactive ingredients, such as cordycepin, D-mannitol, polysaccharides, and N6-(2-hydroxyethyl)-adenosine (HEA), have received increasing attention due to their antitumor, antioxidant, antidiabetic, radioprotective, antiviral and immunomodulatory activities. Here, we systematically sorted out the latest research progress on the chemical characteristics, biosynthetic gene clusters and pathways of these four typical bioactive ingredients. This summary will lay a foundation for obtaining low-cost and high-quality bioactive ingredients in large amounts using microbial cell factories in the future.